In Vivo Evaluation of the Acute Pulmonary Response to Poractant Alfa and Bovactant Treatments in Lung-Lavaged Adult Rabbits and in Preterm Lambs with Respiratory Distress Syndrome - Francesca Ricci; Fabrizio Salomone; Elke Kuypers; Daan Ophelders; Maria Nikiforou; Monique Willems; Tobias Krieger; Xabier Murgia; Matthias Hütten; Boris W. Kramer; Federico Bianco (Frontiers Media S.A., 2017)
BackgroundPoractant alfa (Curosurf®) and Bovactant (Alveofact®) are two animal-derived pulmonary surfactants preparations approved for the treatment of neonatal respiratory distress syndrome (nRDS). They differ in their source, composition, pharmaceutical form, and clinical dose. How much these differences affect the acute pulmonary response to treatment is unknown.ObjectivesComparing these two surfactant preparations in two different animal models of respiratory distress focusing on the short-term response to treatment.MethodsPoractant alfa and Bovactant were administered in a 50-200 mg/kg dose range to surfactant-depleted adult rabbits with acute respiratory distress syndrome induced by lavage and to preterm lambs (127-129 days gestational age) with nRDS induced by developmental immaturity. The acute impact of surfactant therapy on gas exchange and pulmonary mechanics was assessed for 1 h in surfactant-depleted rabbits and for 3 h in preterm lambs.ResultsOverall, treatment with Bovactant 50 mg/kg or Poractant alfa 50 mg/kg did not achieve full recovery of the rabbits' respiratory conditions, as indicated by significantly lower arterial oxygenation and carbon dioxide values. By contrast, the two approved doses for clinical use of Poractant alfa (100 and 200 mg/kg) achieved a rapid and sustained recovery in both animal models. The comparison of the ventilation indices of the licensed doses of Bovactant (50 mg/kg) and Poractant alfa (100 mg/kg) showed a superior performance of the latter preparation in both animal models. At equal phospholipid doses, Poractant alfa was superior to Bovactant in terms of arterial oxygenation in both animal models. In preterm lambs, surfactant replacement therapy with Poractant alfa at either 100 or 200 mg/kg was associated with significantly higher lung gas volumes compared to Bovactant treatment with 100 mg/kg.ConclusionAt the licensed doses, the acute pulmonary response to Poractant alfa was significantly better than the one observed after Bovactant treatment, either at 50 or at 100 mg/kg dose, in two animal models of pulmonary failure.